Modulation of upper limb joint work and power during sculling while ballasted with varying loads - Lauer, J.; Rouard, A. H.; Vilas-Boas, J. P. (The Journal of Experimental Biology, 2017)
The human musculoskeletal system must modulate work and power output in response to substantial alterations in mechanical demands associated with different tasks. In particular, in water, upper limb muscles must perform net positive work to replace the energy lost against the dissipative fluid load. Where in the upper limb are work and power developed? Is mechanical output modulated similarly at all joints, or are certain muscle groups favored? This study examined, for the first time, how work and power per stroke are distributed at the upper limb joints in seven male participants sculling while ballasted with 4, 6, 8, 10 and 12 kg. Upper limb kinematics was captured and used to animate body virtual geometry. Net wrist, elbow and shoulder joint work and power were subsequently computed through a novel approach integrating unsteady numerical fluid flow simulations and inverse dynamics modeling. Across a threefold increase in load, total work and power significantly increased from 0.38±0.09 to 0.67±0.13 J kg-1, and 0.47±0.06 to 1.14±0.16 W kg-1, respectively. Shoulder and elbow equally supplied >97% of the upper limb total work and power, coherent with the proximo-distal gradient of work performance in the limbs of terrestrial animals. Individual joint relative contributions remained constant, as observed on land during tasks necessitating no net work. The apportionment of higher work and power simultaneously at all joints in water suggests a general motor strategy of power modulation consistent across physical environments, limbs and tasks, regardless of whether or not they demand positive net work.